Interaction Of Zinc With Aflatoxin With Reference To Serum Biochemical Profile Of Broiler Chicken - Shamsudeen, P.; Shrivastava , HP. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A biological experiment was conducted to evaluate the interactive effects of organic and inorganic zinc (Zn) supplementation with aflatoxin (AF) on serum biochemical parameters of broilers. The result indicated that the serum albumin, cholesterol, globulin, glucose and total protein were significantly decreased by dietary AF, whereas the level of SGOT and SGPT increased numerically due to dietary AF. The supplementation of Zn in chelated or inorganic form marginally improved the level of albumin, cholesterol level, glucose and total protein whereas significantly reduced the level of SGOT and SGPT.
Keywords: Aflatoxin; zinc; serum biochemical profile; broiler